Structural basis for the RNA binding selectivity of oligonucleotide analogues containing alkylsulfide internucleoside linkages and 2'-substituted 3'-deoxyribonucleosides. - Damha, M J (1995)
In this report we describe the synthesis of oligonucleotides containing sulfide-linked dinucleoside units, namely rT(2'OH)sdT, rT(2'OMe)sdT, dTsrU(2'OMe) and dT(2'OMe)srU(2'OMe). We also describe the interactions of such oligomers with complementary DNA and RNA targets, and provide the structural basis for their remarkable RNA binding selectivity. In all cases, the Tm values of the S/P-chimera duplexes were lower than those of the corresponding unmodified duplexes. We attribute this to steric interactions between the 5'sulfur and the atoms of the nearby base/sugar residues. The 2'-substituents (i.e., 2'OH or 2'OMe) vicinal to the alkylsulfide internucleoside linkage significantly perturb the structure and stability of the duplexes formed with DNA, and more so than with RNA. The introduction of three rT(2'OH)sdTp (or rT(2'OMe)sdTp) units into an oligodeoxynucleotide sequence was sufficient to abolish binding to complementary DNA but not RNA. The same three substitutions with dTsrU(2'OMe)p and dT(2'OMe)srU(2'OMe)p did not abolish binding to DNA but the resulting complexes had poor thermal stability. The RNA-binding 'selectivity' exhibited by these oligomers is attributed to the tendency of the 2'-substituted (branched) furanoses to adopt the C3'-endo pucker, a conformation that is inconsistent with the B-form structure of helical DNA. The preference of these sugars to exist often exclusively in the C3'-endo form is attributed to stereoelectronic effects, namely gauche and anomeric effects. Our findings support the hypothesis that nucleoside analogues puckered exclusively in the C3'-endo form may result in them being especially good binders of targeted mRNA [S.H. Kawai (1991), Ph.D. Thesis, McGill University; Kawasaki et al. (1993) J. Med. Chem. 36, 831-841].